Hospital admissions for dementia in the Brazilian public health system over the last decade - Alberto Fernando Oliveira Justo; Natalia Gomes Gonçalves; Adriana Nancy Medeiros Dos Santos; Regina Silva Paradela; Márlon Juliano Romero Aliberti; Cleusa Pinheiro Ferri; Claudia Kimie Suemoto (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract OBJECTIVE The rise in dementia prevalence, particularly in lower‐ and middle‐income countries (LMIC), places a significant burden on healthcare systems. However, comprehensive data on dementia hospital admissions are scarce. METHODS We analyzed admission rates for dementia, cost of hospital admissions, lengths of hospital stay, and in‐hospital deaths in 2010 and 2019 in Brazil. RESULTS Admission rates declined from 19.7/100,000 inhabitants in 2010 to 14.6/100,000 in 2019. In‐hospital mortality increased from 3.9% in 2010 to 8.8% in 2019, particularly for short‐term stays. Although 9.6% of hospital admissions occurred in regions with lower economic power in 2010 and 10.4% in 2019, these regions had higher mortality, reaching 4.3% of in‐hospital deaths in 2010 and 9.3% in 2019. CONCLUSION The observed trends, alongside sex and regional disparities, underscore the need for targeted investment in healthcare infrastructure and training to improve dementia care in LMIC. Highlights The rate of hospital admissions for dementia was similar in 2010 and 2019 in Brazil. The cost per hospital admission in 2010 decreased by 38.5% compared with 2019. There was an increase in short‐term hospital stays for dementia in 2019 compared to 2010, accompanied by an increase in mortality rates for these short‐term stays. While hospital admissions for dementia decreased in men and increased in women, the in‐hospital mortality due to dementia increased for both sexes.